The last wife - Hamilton, Karen (Karen J.) (Graydon House, 2020)
"Nina and Marie were best friends - until Nina was diagnosed with a terminal illness. Before she died, Nina asked Marie to fulfill her final wishes. But her mistake was in thinking Marie was someone she could trust. What Nina didn't know was that Marie always wanted her beautiful life, and that Marie has an agenda of her own. She'll do anything to get what she wants. Marie thinks she can keep her promise to her friend's family on her own terms. But what she doesn't know is that Nina was hiding explosive secrets of her own..."--Publisher description.